2018
DOI: 10.2478/jas-2018-0018
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Uniqueness of Honeybee Apis Cerana from the Korean Peninsula Inferred from The Mitochondrial, Nuclear, and Morphological Data

Abstract: Apis cerana is an Eastern honeybee species distributed throughout Asia and closely related to the Western honeybee species Apis mellifera distributed across all of Africa, Europe and Western Asia, and subdivided into thirty confirmed subspecies. Currently, A. cerana is an endangered bee species in contrast to A. mellifera. We sequenced and annotated the complete mitochondrial genome of A. cerana from the Jeollanam-do province of South Korea and uploaded to the DDBJ/Genbank database(AP018431). MtDNA sequence is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…Plus, the COI sequences provide strong evidence that these are different species, with a 7.7-8.6% genetic distance between the two species. This genetic distance matches the level of genetic divergence of mtDNA between animal species (8-17%) [34]. This indicates that cryptic species may exist in Scolia and male genitalia and DNA barcoding are useful in recognizing these species.…”
Section: Tribe Scoliinisupporting
confidence: 69%
“…Plus, the COI sequences provide strong evidence that these are different species, with a 7.7-8.6% genetic distance between the two species. This genetic distance matches the level of genetic divergence of mtDNA between animal species (8-17%) [34]. This indicates that cryptic species may exist in Scolia and male genitalia and DNA barcoding are useful in recognizing these species.…”
Section: Tribe Scoliinisupporting
confidence: 69%
“…ACNC105, ACNC106, ACNC107, ACNC108, ACNC109) subdivided into Group A and Group B (Lee et al, 2016). Ilyasov et al (2018a) found one more new haplotype ACNC110 in A. c. koreana. In the current study, we found new haplotype ACNC111 of Russian Far East A. cerana, which was very similar to A. c. koreana but differed from it by one insertion 31insT, with number of position relatively the sequence KP064870.…”
mentioning
confidence: 85%
“…The NC1 region of the Russian Far East A. cerana was found to be similar to the A. cerana ACNC101 haplotype and differed from the Korean A. c. koreana samples KP064870 and KP064972 by only one insertion 31insT, relatively to the NC1 sequence of Russian Far East A. cerana. Ten A. cerana haplotypes of the NC1 region (ACNC101 -ACNC110) were published earlier (Lee et al, 2016;Ilyasov et al, 2018a). This haplotype with 31insT insertion is new and is named ACNC111 (Fig.…”
Section: Variation In the Complete Mtdnamentioning
confidence: 99%
“…The subspecies A. m. jemenitica, A. m. adansonii cannot be discriminated by morphometry ( Radloff et al, 1998 ) but can be discriminated by other morphometry ( Ruttner, 1988 , Dukku, 2016 ), by mtDNA ( Franck et al, 2001 ). The subspecies A. m. carpathica , A. m. carnica , A. m. macedonica cannot be discriminated by morphometry ( Radloff et al, 1998 ) but can be discriminated by other morphometry ( Foti et al, 1965 , Engel, 1999 , Cauia et al, 2008 , Mărghitas et al, 2008 , Teleky et al, 2009 ), by mtDNA ( Mărghitas et al, 2009 , Bouga et al, 2011 , Coroian et al, 2014 , Syromyatnikov et al, 2018 ; Ilyasov et al, 2018 ). The subspecies A. m. rodopica , A. m. macedonica cannot to be discriminated by morphometry ( Engel, 1999 ), by allozyme ( Bouga et al, 2005 , Kandemir et al, 2005 , Ivanova et al, 2010 ), but can be discriminated by other morphometry ( Foti et al, 1965 , Engel, 1999 , Cauia et al, 2008 , Mărghitas et al, 2008 , Teleky et al, 2009 ), by mtDNA ( Lazarov, 1936 , Tzonev, 1960 , Velichkov, 1970 , Bouga et al, 2011 ), by microsatellites ( Nikolova, 2011 , Uzunov et al, 2014 ), by mtDNA ( Bouga et al, 2005 , Martimianakis et al, 2011 ; Meixner et al, 2013 ; Radoslavov et al, 2017 ).…”
Section: The Current Taxonomic Pattern Of the Honey Bee A mentioning
confidence: 99%
“…The subspecies A. m. syriaca , A. m. anatoliaca, A. m. meda assigned to the O lineage by morphometry ( Ruttner, 1988 ), by mtDNA ( Arias and Sheppard, 1996 ), but assigned to the A lineage (Z sublineage) by mtDNA ( Arias and Sheppard, 1996 , Franck et al, 2000 , Bouga et al, 2005 ; Alburaki et al, 2011 , Alburaki et al, 2013 ). The subspecies A. m. caucasia assigned to the O lineage by morphometry ( Ruttner, 1988 , Adl et al, 2007 , Meixner et al, 2007 , Kandemir et al, 2011 ), but assigned to the C lineage by mtDNA ( Franck et al, 2000 ; Alburaki et al, 2011 , Alburaki et al, 2013 ), by allozyme ( Smith, 1991 ; Garnery et al, 1992 ; Kandemir and Kence, 1995 , Ivanova et al, 2011 ), by mtDNA ( Cornuet and Garnery, 1991 , Koulianos and Crozier, 1997 , Smith et al, 1997 , Garnery et al, 1998 , Palmer et al, 2000 , Franck et al, 2000 , Smith, 2002 , Özdïl et al, 2009 , Mărghitas et al, 2009 ; Ilyasov et al, 2018 ). The subspecies A. m. cypria , A. m. adami assigned to the O lineage by morphometry ( Ruttner, 1988 ) but assigned to the C lineage by mtDNA and allozyme ( Bouga et al, 2005 ).…”
Section: The Current Taxonomic Pattern Of the Honey Bee A mentioning
confidence: 99%